The Effect of ODOI On Innovative Work Behavior And Employee Performance - Luhgiatno, Widaryanti; Widaryanti; Aprih Santoso (Jurnal Manajemen, 2022)
The research objective is to develop optimal distinctive open innovation (ODOI) concepts, propositions and indicators as well as to test them empirically. ODOI was formed using a synthesis method of two concepts, namely optimal characteristics, derivatives of social identity theory, and open innovation derived from innovation theory. Quantitative empirical testing using SEM on primary data, the PTS lecturers in the LLDIKTI VI Central Java environment were 190 respondents. The test results show that ODOI is able to mediate the effect of innovative work behaviour on improving employee work performance. Innovative work behavior has an effect on increasing ODOI and has an effect on improving employee work performance. ODOI has an effect on improving employee work performance.